If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(7x + -9) = 67x + 7v * 8x Reorder the terms: 7(-9 + 7x) = 67x + 7v * 8x (-9 * 7 + 7x * 7) = 67x + 7v * 8x (-63 + 49x) = 67x + 7v * 8x Reorder the terms for easier multiplication: -63 + 49x = 67x + 7 * 8v * x Multiply 7 * 8 -63 + 49x = 67x + 56v * x Multiply v * x -63 + 49x = 67x + 56vx Reorder the terms: -63 + 49x = 56vx + 67x Solving -63 + 49x = 56vx + 67x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56vx' to each side of the equation. -63 + -56vx + 49x = 56vx + -56vx + 67x Combine like terms: 56vx + -56vx = 0 -63 + -56vx + 49x = 0 + 67x -63 + -56vx + 49x = 67x Add '-67x' to each side of the equation. -63 + -56vx + 49x + -67x = 67x + -67x Combine like terms: 49x + -67x = -18x -63 + -56vx + -18x = 67x + -67x Combine like terms: 67x + -67x = 0 -63 + -56vx + -18x = 0 Add '63' to each side of the equation. -63 + -56vx + 63 + -18x = 0 + 63 Reorder the terms: -63 + 63 + -56vx + -18x = 0 + 63 Combine like terms: -63 + 63 = 0 0 + -56vx + -18x = 0 + 63 -56vx + -18x = 0 + 63 Combine like terms: 0 + 63 = 63 -56vx + -18x = 63 Reorder the terms: -63 + -56vx + -18x = 63 + -63 Combine like terms: 63 + -63 = 0 -63 + -56vx + -18x = 0 Factor out the Greatest Common Factor (GCF), '-1'. -1(63 + 56vx + 18x) = 0 Ignore the factor -1.Subproblem 1
Set the factor '(63 + 56vx + 18x)' equal to zero and attempt to solve: Simplifying 63 + 56vx + 18x = 0 Solving 63 + 56vx + 18x = 0 Move all terms containing x to the left, all other terms to the right. Add '-63' to each side of the equation. 63 + 56vx + -63 + 18x = 0 + -63 Reorder the terms: 63 + -63 + 56vx + 18x = 0 + -63 Combine like terms: 63 + -63 = 0 0 + 56vx + 18x = 0 + -63 56vx + 18x = 0 + -63 Combine like terms: 0 + -63 = -63 56vx + 18x = -63 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 2x+2y+1+6y+x-6=180 | | 1/3x=-2/5 | | x+5x=336 | | 7/3+6x=2/3-7x | | 8x+16y+z=400 | | 4/e^3x | | 1.0047*8.2= | | 2(x+4)=3(2x-4) | | 2sin^2x=5cos^2x-3 | | Y=-.025x^2+x+6 | | x+2=2x+8 | | 4y+1=1 | | 4sin^2(2x)-2=0 | | 2ln(x+3)-3=0 | | 3x+2=-7+6x | | -4x-8x=-5-103 | | sec^2=2tan | | x+8x=-7+34 | | 5c+2=2c-7 | | 44=-6x+8 | | 5x-7x=3-5 | | -4x-2=23 | | -31=8x-(2x-5) | | 3(8x+16)-12=2+(7-3x) | | 4x^2-8x^2-96=0 | | 54(x^2+3)=0 | | (-7x/3)-1=-1-(7x/8) | | 35=x+(2x-1)+(2+14x) | | 4x-10+7(x-3)=0 | | 6(2+7x)+3x=9+6(9+8x) | | (2x+4y)+(2x-y)-(x-2y)= | | 16-(3x-15)=4x-(9x-9) |